PENGARUH KEPERCAYAAN, KEMUDAHAN DAN PERSEPSI RISIKO MENGGUNAKAN E-COMMERCE TERHADAP KEPUTUSAN PEMBELIAN ONLINE DI TOKOPEDIA.COM - Yunita Fitri Wahyuningtyas; Marlina Sari Weasaga (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2022)
This study aims to find out the influence of convenience and risk perception, both racially and simultaneously on online purchasing decisions at tokopedia.com. This study used a quantitative approach by collecting data through a survey method. The population in this study were users of tokopedia.com in the Umbulharjo area of Yogyakarta City. The sampling technique used a purposive sampling method, which is based on the criteria of tokopedia.com users in the Umbulharjo area of Yogyakarta City who has purchased online at tokopedia.com. A sample of 100 respondents with data collection techniques using a questionnaire. The validity test of the instrument used confirmatory factor analysis, while the reliability test used Cronbach alpha. The analysis technique used is multiple linear regression analysis. The results of this study indicate that: (1) Trust has a positive effect on purchasing decisions, as evidenced by the t value of 2.784 with a significance value of 0.006 less than 0.05 and the regression coefficient having a positive value of 0.189. (2) convenience has a positive effect on purchasing decisions, as evidenced by the t value of 5.406 with a significance value of 0.000 less than 0.05 and the regression coefficient having a positive value of 0.346. (3) perceived risk has a positive effect on purchasing decisions, as evidenced by the t value of 4,848 with a significance value of 0.000 less than 0.05 and the regression coefficient having a positive value of 0.287. (4) Trust, Convenience and Risk Perception simultaneously have a positive effect on purchasing decisions, as evidenced by the results of F count of 74.526 greather than 2.70 with a significance of 0.000. (5) The magnitude of the influence of Trust, Convenience, and Risk Perception on purchasing decisions (Adjusted R Square) is 69%. The regression equation obtained is Y = 4.548 + 0.189X₁ + 0.346X₂ + 0.287X₃ + e.